2019
DOI: 10.1002/solr.201900338
|View full text |Cite
|
Sign up to set email alerts
|

Loss Analysis in Perovskite Photovoltaic Modules

Abstract: Hybrid metal-halide perovskite-based thin-film photovoltaics (PVs) have the potential to become the next generation of commercialized PV technology with certified power conversion efficiencies reaching 24% on devices having 0.1 cm 2 area. Recent efforts in upscaling this technology result in an efficiency of 12.6% for 354 cm 2 modules. However, upscaling loss for perovskite-based PVs is higher than for any other PV technology. In this study, upscaling losses of devices with aperture area 0.1, 4, and 100 cm 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…The same trend is also visible with fill factor (FF), but not with V OC and J SC . The variation in results of the samples is due to the sample‐to‐sample and batch‐to‐batch variations of spin‐coated solar modules, as discussed in our previous work 5 …”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…The same trend is also visible with fill factor (FF), but not with V OC and J SC . The variation in results of the samples is due to the sample‐to‐sample and batch‐to‐batch variations of spin‐coated solar modules, as discussed in our previous work 5 …”
Section: Resultsmentioning
confidence: 82%
“…The highest GFF achieved is 95% 9,16 using ps pulsed laser patterning. Hence, the module inactive area loss is 5% or more, making this the second most significant loss mechanism after layer inhomogeneity loss 5 . In this work, we show how an inactive area loss can be decreased from 5% to 1% by optimizing the design of the module to point contact interconnections 17 and processing perovskite modules with 98.5% and 99% GFF.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…With regard to the P3 patterning step, it has been reported that flaking, or the formation of large metal flakes or particles of top metal electrode, causes problems with the electrical isolation of the series interconnected sub-cells in modules [ 20 ]. The flaking causes fluctuations in the maximum power point (MPP) tracking under continuous 1-sun illumination, which result in a reduction in module performance and long-term stability due to intermittent lack of contact with the sub-cells [ 21 ]. To decrease the possibility of flaking of the metal electrode, several strategies have been applied, such as optimization of nanosecond or picosecond laser pulse, and wider P3 scribing with multiple time overlapping [ 16 ].…”
Section: Introductionmentioning
confidence: 99%